2009
DOI: 10.1111/j.1525-1594.2009.00895.x
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits of High‐flow Management in Children With Pulmonary Atresia

Abstract: The high-flow management of cardiopulmonary bypass (CPB; >or=2.4 L/min/m(2)) is a standard strategy used at this institute for children with pulmonary atresia (PA) due to a fear that the blood flow may be diverted by the major/minor aortopulmonary-collateral-arteries and hypervascularization due to long-term hypoxia. The purpose of this study was to describe the validity of high-flow management in children with PA. The CPB records of 23 children with PA who underwent a definitive biventricular repair between F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Cardiopulmonary bypass is required for the vast majority of surgically corrective procedures undertaken within an open heart and on the great vessels. Recent work by Fujii et al 7 has shown that paediatric patients require far higher cardiac indexes than traditionally given to adult patients, especially those with cyanotic heart disease. This is reflected in our retrospective data (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Cardiopulmonary bypass is required for the vast majority of surgically corrective procedures undertaken within an open heart and on the great vessels. Recent work by Fujii et al 7 has shown that paediatric patients require far higher cardiac indexes than traditionally given to adult patients, especially those with cyanotic heart disease. This is reflected in our retrospective data (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Yasuhiro Fujii et al. (70) of Okayama University Hospital, Okayama City, Okayama, Japan described the validity of high‐flow management in children with pulmonary atresia (PA). The CPB records of 23 children with PA who underwent a definitive biventricular repair were retrospectively reviewed.…”
Section: Cardiopulmonary Support and Membrane Oxygenationmentioning
confidence: 99%
“…Our special thanks go to Angela T. Hadsell, Executive Editor, and Paul S. Malchesky, DEng, Editor‐in‐Chief, for making this possible. We have already published several manuscripts covering all areas of pediatric cardiopulmonary bypass and mechanical circulatory support systems in terms of clinical (1–10), basic science (11–13), and engineering (14–23) applications in the November 2009 Special Issue of Artificial Organs .…”
mentioning
confidence: 99%